In vivo accuracy of conventional and digital radiographic methods in confirming root canal working length determination by Root ZX (Journal of Applied Oral Science, 2012)
OBJECTIVES: To compare, in vivo, the accuracy of conventional and digital radiographic methods in determining root canal working length. MATERIAL AND METHODS: Twenty-five maxillary incisor or canine teeth from 22 patients were used in this study. Considering the preoperative radiographs as the baseline, a 25 K file was inserted into the root canal to the point where the Root ZX electronic apex locator indicated the APEX measurement in the screen. From this measurement, 1 mm was subtracted for positioning the file. The radiographic measurements were made using a digital sensor (Digora 1.51) or conventional type-E films, size 2, following the paralleling technique, to determine the distance of the file tip and the radiographic apex. RESULTS: The Student "t" test indicated mean distances of 1.11 mm to conventional and 1.20 mm for the digital method and indicated a significant statistical difference (p